USûL-İ FIKHIN KELAMÎ KAYNAĞINI YENİDEN DEĞERLENDİRMEK - Salim Öğüt (İslami İlimler Dergisi)
İt is stated that disciplines on which science of usul al-fiqh depends are theology, linguistics and law. Among them theology is priority one from the point of its function. Because rules that are projected gain validity only when they are based on the will of a creator who has wisdom and science. Establishing this is among the duties of theology discipline. İn this article, theological bases of usul al-fiqh thought are empasized. Also in this study, problems that negligence of theological bases in the modern period caused from the point of fiqh thought are touched.